Characterization of Simplicia, Extract, and Mineral Content of Broccoli (Brassica oleracea var. italica) - Bina Lohita Sari; Zaldy Rusli; Ananda Putri Kalista (Helium: Journal of Science and Applied Chemistry, 2025)
Bioactive compounds and minerals in medicinal plants make them both therapeutic agents and raw materials for producing contemporary medications. Broccoli (Brassica Oleracea var Italica) is one of the possible therapeutic plants that features several nutrients that are high in minerals. This study produced Broccoli ethanol extract and characterized the water, ash, and phytochemical test of simplicia and extract. The mineral content of simplicia, such as calcium, potassium, sodium, and iron, used the flame test Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) method. This method is specifically for analyzing atomic elements or ions, which causes them to be excited and emit light at specific wavelengths. The result of water and ash content of Broccoli simplicia and ethanol extract within a range of values 2-9 – 5.8 %. Positive results for alkaloids, flavonoids, saponins, and tannins in phytochemical tests of simplicia and ethanol extract. The mineral content showed that calcium, potassium, sodium, and iron were 109.52 ± 0.25 mg/100 g, 375.58 ± 0.81 mg/100 g, 9.54 ± 0.092 mg/100 g, and 1.93 ± 0.00 mg/100g, respectively. It was concluded that as a natural ingredient, broccoli contains higher potassium than other minerals, and secondary metabolites in simplex and ethanol extracts have health benefits.